Investor sentiment, flight-to-quality, and corporate bond comovement - Sebastian Bethke; Monika Gehde-Trapp; Alexander Kempf (University of Cologne, Centre for Financial Research (CFR), 2015)
We examine the dynamics of bond correlation using a broad sample of US corporate bonds, and document that bond correlation varies heavily over time. We attribute this variation in bond correlation to variation in risk factor correlation reflecting time-varying flight-to-quality behavior of investors. We show that risk factor correlation increases when investor sentiment decreases, i.e., corporate bond investors exhibit stronger flight-to-quality when their sentiment is low. Thus, low investor sentiment leads to flightto- quality behavior and, ultimately, high bond correlation.
Keywords: G11; G12; 330; bond correlation; risk factor correlation; flight-to-quality; investor sentiment